2020
DOI: 10.7150/ijbs.45498
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Endocytic Pathway and Autophagy Process as a Novel Therapeutic Strategy in COVID-19

Abstract: Coronaviruses (CoVs) are a group of enveloped, single-stranded positive genomic RNA viruses and some of them are known to cause severe respiratory diseases in human, including Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome (MERS) and the ongoing coronavirus disease-19 (COVID-19). One key element in viral infection is the process of viral entry into the host cells. In the last two decades, there is increasing understanding on the importance of the endocytic pathway and the autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
457
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(468 citation statements)
references
References 69 publications
5
457
0
6
Order By: Relevance
“…Both SARS-CoV-1 and -2 engage angiotensin-converting enzyme 2 (ACE2) as their plasma membrane receptor (20)(21)(22) . Upon binding, the viruses along with the receptor are endocytosed into the cell into a low pH endosomal compartment where there are proteases, including cathepsins, that can cleave Spike and allow for entry into the cytosol (23)(24)(25). Since cathepsins require a low pH for activity, chloroquine and its derivatives that neutralize this low pH can effectively block viral entry (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SARS-CoV-1 and -2 engage angiotensin-converting enzyme 2 (ACE2) as their plasma membrane receptor (20)(21)(22) . Upon binding, the viruses along with the receptor are endocytosed into the cell into a low pH endosomal compartment where there are proteases, including cathepsins, that can cleave Spike and allow for entry into the cytosol (23)(24)(25). Since cathepsins require a low pH for activity, chloroquine and its derivatives that neutralize this low pH can effectively block viral entry (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding, the viruses along with the receptor are endocytosed into the cell into a low pH endosomal compartment where there are proteases, including cathepsins, that can cleave Spike and allow for entry into the cytosol (23)(24)(25). Since cathepsins require a low pH for activity, chloroquine and its derivatives that neutralize this low pH can effectively block viral entry (23)(24)(25). Recent studies have also identified a plasma membrane-associated serine protease, TMPRSS2, is active against Spike, cleaving the protein extracellularly thereby bypassing the requirement for endosomal proteases (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng indicated that SARS-CoV-2 is an emerging new coronavirus that causes a global threat, and summarized the key events occurred during the early outbreak, the basic characteristics of the pathogen, the signs and symptoms of the infected patients, the possible transmission pathways of the virus, the Zhou and Zhao pointed out the great importance of using therapeutic neutralizing antibodies (NAbs) to control the spread and re-emergence of SARS-CoV-2 and assert that the development of NAbs therefore should be a high priority in near future [5]. Yang and Shen discussed the implication of the endocytic pathway and autophagy in viral infection and how novel therapeutic approaches could be developed by targeting these processes for treatment of COVID-19 [6].…”
mentioning
confidence: 99%
“…Interestingly, it has been recognized that HMGB1 regulates autophagy [10] and could potentially be a biomarker of acute lung injury [11]. Autophagy is one of the mechanisms involved in COVID-19 and is involved in viral entry and replication in cells, so targeting this pro-Street Horm Res Paediatr 2 DOI: 10.1159/000508291 cess has been suggested as a possible novel therapeutic strategy for COVID-19 [12].…”
mentioning
confidence: 99%